PERILAKU KONSUMSI SERAT PADA MAHASISWA ANGKATAN 2020 FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS ISLAM NEGERI SUMATERA UTARA TAHUN 2023 - Nabila Isma Zahra; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
The behavior of fiber consumption until now is still quite low among the public. Though fiber is a component that is important enough for the body to maintain health and as a prevention of disease. Moreover, for students whose majority live in diost, they do not really care about the adequacy of fiber that must be consumed according to daily fiber needs due to several factors, one of which is economic factors in boarding children. This study aims to determine the theory of planned behavior, which focuses on attitudes based on beliefs, namely attitudes, subjective norms, perceptions of control and intentions of students of the class of 2020 Faculty of Public Health, State Islamic University of North Sumatra towards fiber consumption behavior in accordance with daily needs. This research is qualitative research. This research was conducted at the Faculty of Public Health, State Islamic University of North Sumatra. Sampling techniques using purposive sampling with informant criteria, namely students who live in boarding houses, active students of the faculty of public health. The informant of this research consisted of 5 main informants and 1 key informant. Research data is primary data collected by the in-depth waancra method. The results showed that students had a positive attitude towards fiber consumption behavior. Subjective norms come from the family but in this context the mother is more dominant in influencing. The perception of control possessed by students is low perception of control, all students have good and positive intentions for fiber consumption as needed.